DEVELOPMENT OF A SMART IOT-BASED MONITORING SYSTEM FOR FERTIGATION AND SEED WEIGHT DETECTION IN SACHA INCHI - Prasetyo, Tri Ferga; Purwanto, Muhamad Dendi; Sujadi, Harun; Andayani, Sri (LPPM Nusa Mandiri, 2025)
This research focuses on designing a fertilization monitoring system based on the Internet of Things (IoT) and detecting the weight of Sacha Inchi plant seeds. The two tools are integrated with IoT platforms, enabling remote monitoring and control via the Simosachi app. Test results indicate that the system provides accurate data on soil and plant conditions, allowing farmers to make informed decisions on fertilization and irrigation. The seed weight detection tool also functions well, with a minor error margin still within acceptable limits. With improved monitoring and control of the fertilization process, as well as accurate monitoring of crop yields, the system is expected to help farmers achieve more optimal harvests. The seed weight detection tool achieved an accuracy of 97.94%, surpassing similar prior systems in terms of real-time data integration and multi-parameter monitoring. Future research may focus on enhancing the accuracy of the seed weight detection tool and developing advanced fertigation control algorithms